Współczesne racjonalizowanie mitów. Klątwa królowej Pazyfae w nowożytnej prozie polskiej - Nawrocka, Weronika (Zagadnienia Rodzajów Literackich, 2024)
Greek myths, which undoubtedly constitute one of the most important pillars of European culture, have always been a source of inspiration for artists. The original heroes were archetypal figures, and their purpose was to attempt to explain the functioning of the world and universal human values even in ancient times. However, the characters presented by later creators will always reflect the times of the author. To what extent, though, can one modify, change, or remove their fundamental characteristics? In my essay, I focus on presenting a phenomenon increasingly encountered in literature, which ancient stories of gods, kings, and heroes also did not avoid, namely: rewriting classical stories according to contemporary ideologies and theories. For analysis, I have chosen two contemporary stories written by Polish female authors. Both deal with the mythological queen of Crete, Pasiphae. After analyzing the stories, I then compare them with the original texts, dating back to times before our era. I come to the conclusion that it is untrue to claim, as commonly stated, that there is a lack of female characters in mythology — the problem lies in their later adaptations, not in the authentic stories. With that being said, in my essay, I attempt to present the character of Pasiphae in her full femininity, as she was seen in antiquity, unrestricted by any social norms.